The relationship between Malaysia’s residential property price index and residential properties loan supply - Law, Chee-Hong; Lim, Ghee-Thean (Universiti Sains Malaysia, 2016)
This paper aims to examine the linkages between residential properties prices and residential properties loans in Malaysia from 1999 to 2015, in addition to income level and the impact of the economic crisis. Even though residential properties are a basic necessity, there is no previous study that attempts to estimate the long-run and short-run relationship between loans and price level in residential properties in Malaysia. It is believed that property price level moves in the same direction as loan supply. The estimations are divided into two parts: the detection of long run relationships and the estimation the long-run and short-run elasticities from an ARDL model. The results support the hypothesis that the loan supply has a positive impact on the residential price levels; the robustness test also supports this conclusion. This implies the importance of closely monitoring the housing loan activities of banks to control residential property prices.